SUPERVISI KEPEMIMPINAN PENGASUH SEBAGAI UPAYA PENINGKATAN KOMPETENSI MENGAJAR DAN PENDIDIKAN KARAKTER DI TAMAN PENDIDIKAN AL-QUR’AN MASJID AL-HIKMAH LAWEYAN SURAKARTA - Yunadi, Ridwan Rohmad; Muflih, Roid Shalahuddin; Musthofa, Aziz; Saifurrohman, Muhammad; Abbas, Ngatmin (Jurnal Manajemen Pendidikan, 2025)
This study aims to describe the educational supervision strategy in teaching the Qur'an at TPQ Masjid Al-Hikmah, Gentan, Laweyan, Solo. The background of this research is the important role of supervision in improving the effectiveness of learning, especially in non-formal educational institutions such as TPQ. This research uses a descriptive qualitative approach with data collection techniques through interviews, observation, and documentation of three TPQ teachers. The results show that supervision is carried out in a structured manner through the division of tasks based on teacher competence, selection of learning methods that are in accordance with the characteristics of students, and continuous learning evaluation. The supervision strategy has a positive impact on teacher motivation, improving the quality of learning, and achieving student learning outcomes. In conclusion, the supervision model carried out by the head of TPQ plays an important role in creating effective, meaningful and character-oriented learning as well as the ability to read and memorize the Qur'an properly and correctly. Unlike other studies that focus on formal educational institutions, this research focuses on informal institutions, namely TPQ. Non-formal institutions are just as important as formal educational institutions.